2009
DOI: 10.1021/bi801759a
|View full text |Cite
|
Sign up to set email alerts
|

Combined Microspectrophotometric and Crystallographic Examination of Chemically Reduced and X-ray Radiation-Reduced Forms of Cytochrome ba3 Oxidase from Thermus thermophilus: Structure of the Reduced Form of the Enzyme

Abstract: Three paths are described to obtain crystals of reduced (II-E4Q/I-K258R) cytochrome ba 3 , and the structures of these are reported at ∼2.8 to 3.0 Å resolution. Microspectrophotometry of single crystals of Thermus ba 3 oxidase at 100 K was used to show that crystals of the oxidized enzyme are reduced in an intense X-ray (beam line 7-1 at the Stanford Synchrotron Radiation Laboratory, U.S.A) being nearly complete in one minute. The previously reported structures of ba 3 (PDB codes 1EHK and 1XME), having a cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
85
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(90 citation statements)
references
References 37 publications
4
85
1
Order By: Relevance
“…The other remarkable feature of the O 2 reduction mechanism in ba 3 is the fast P I formation and heme b oxidation (approximately 5 μs) in both the absence of CO (this study) and the presence of CO (our assignment) (6). This rate is approximately 10 times faster than the corresponding rate reported for the bovine enzyme (2,22) and may arise from a shorter distance between heme a 3 and Cu B in ba 3 (23,24) or a redox potential difference that favors electron transfer from heme b 2þ to heme a 3 2þ -O 2 .…”
Section: µSsupporting
confidence: 49%
“…The other remarkable feature of the O 2 reduction mechanism in ba 3 is the fast P I formation and heme b oxidation (approximately 5 μs) in both the absence of CO (this study) and the presence of CO (our assignment) (6). This rate is approximately 10 times faster than the corresponding rate reported for the bovine enzyme (2,22) and may arise from a shorter distance between heme a 3 and Cu B in ba 3 (23,24) or a redox potential difference that favors electron transfer from heme b 2þ to heme a 3 2þ -O 2 .…”
Section: µSsupporting
confidence: 49%
“…The results are consistent with the maintenance of the oxidized protein conformation (36), even though the metal centers are reduced, before annealing at warmer temperature allows the protein to change its structure. The strained configuration shows an interesting spectral feature at 589 nm, also observed in the bovine and thermus CcO irradiated crystals (34,37). Other spectral methods such as single-crystal low-temperature EPR or resonance Raman will be needed to determine the nature of this form; the Soret region of the spectrum, which could provide some clues, absorbs too strongly to be measured (Fig.…”
Section: S142mentioning
confidence: 91%
“…There is evidence that significant reduction of the metal centers occurs (34,35). Therefore, we measured the spectral characteristics of crystals of wild-type and mutant CcO at 100 K using the online microspectrophotometer available at BioCARS, Advanced Photon Source, Argonne National Labs (35).…”
Section: S142mentioning
confidence: 99%
“…However, the structures obtained with conventional synchrotron light sources were determined from protein crystals exposed to a high X-ray flux and high levels of cryoprotectants at cryogenic temperatures. It has been shown in CcO (7,8) as well as other proteins and enzymes (9,10) that the high-intensity synchrotron X-ray beam has many deleterious effects including reduction, ligand dissociation, and damage (11,12). These deleterious effects cause irreversible changes in the protein structure leading to erroneous structural determinations, especially in protein systems containing electron-rich heavy metals (13).…”
mentioning
confidence: 99%
“…These deleterious effects cause irreversible changes in the protein structure leading to erroneous structural determinations, especially in protein systems containing electron-rich heavy metals (13). In oxidized forms of CcO, it has been shown that X-ray reduction of the metal centers occurs even with very short exposures to the X-ray beam (7,14). Deleterious radiation-induced artifacts are especially evident in the structure of the CO-bound derivatives (bCcO-CO) obtained at low temperature by synchrotron radiation in which the X-ray beam has been shown to photodissociate the CO from the heme a 3 iron atom (8).…”
mentioning
confidence: 99%